2016
DOI: 10.1038/ncomms13254
|View full text |Cite
|
Sign up to set email alerts
|

A systems study reveals concurrent activation of AMPK and mTOR by amino acids

Abstract: Amino acids (aa) are not only building blocks for proteins, but also signalling molecules, with the mammalian target of rapamycin complex 1 (mTORC1) acting as a key mediator. However, little is known about whether aa, independently of mTORC1, activate other kinases of the mTOR signalling network. To delineate aa-stimulated mTOR network dynamics, we here combine a computational–experimental approach with text mining-enhanced quantitative proteomics. We report that AMP-activated protein kinase (AMPK), phosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 87 publications
(147 reference statements)
20
112
0
Order By: Relevance
“…S2E, S2F). Indeed, recent work has shown that availability of nutrients concurrently activates AMPK and mTOR (Dalle Pezze et al, 2016). Since mTOR suppresses autophagy, and because autophagy is active between 7–11am in ITAD mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2E, S2F). Indeed, recent work has shown that availability of nutrients concurrently activates AMPK and mTOR (Dalle Pezze et al, 2016). Since mTOR suppresses autophagy, and because autophagy is active between 7–11am in ITAD mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Knowing that AMPK can induce autophagy in mTORC1‐independent pathways27, 28, 29 and that mTORC1 is a negative regulator of autophagy,29 the obtained data suggest a dissociative AMPK‐mTORC1 axis with AMPK sustaining autophagy in KG‐1 cells. In fact, the reports of Sujobert et al and Pezze et al also showed a direct induction of autophagy by AMPK even in the presence of mTORC1 activation 21, 53…”
Section: Discussionmentioning
confidence: 96%
“…A similar contradictory metabolic scenario was already reported in myoblasts in response to amino acids. 53 The authors proposed that the concurrent activation of AMPK and mTORC1 is implicated in the maintenance of protein homoeostasis and on the fuel of metabolites for biosynthetic processes. 53 The relevance of amino acid signalling and mTORC1 PI3K/AKT-independent activation in the context of AML remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In T cells, AAs work as signaling molecules with mTORC1 acting as a key mediator. AAs regulate the intracellular localization and activation of mTORC1 by the lysosome-based signaling system composed of Ras-related GTPases (Rags) and Regulator v-ATPase, GAP activity towards Rags, and folliculin complexes [59, 60]. AAs could protect whole body and muscle from protein loss via mTOR activation and downstream signaling to protein synthesis through mTORC1 in the acute phase of inflammation [61, 62].…”
Section: Amino Acids: Application In Inflammatory Bowel Disease Thmentioning
confidence: 99%